Identification of Shiga-Toxin-Producing Shigella Infections in Travel and Non-Travel Related Cases in Alberta, Canada - Shuai Zhi (MDPI AG, 2021)
It has long been accepted that Shiga toxin (Stx) only exists in Shigella dysenteriae serotype 1. However, in recent decades, the presence of Shiga toxin genes (stx) in other Shigella spp. have been reported. We screened 366 Shigella flexneri strains from Alberta, Canada (2003 to 2016) for stx and 26 positive strains were identified. These isolates are highly related with the majority originating from the Dominican Republic and three isolates with Haiti origin. Both phylogenetic and spanning tree analysis of the 26 Alberta and 29 stx positive S. flexneri originating from the U.S., France, Canada (Quebec) and Haiti suggests that there are geographic specific distribution patterns (Haiti and Dominican Republic clades). This study provides the first comprehensive whole genome based phylogenetic analysis of stx positive S. flexneri strains as well as their global transmission, which signify the public health risks of global spreading of these strains.